Relationship between Personality Traits and Readiness for Substance Abuse - Hossein Mahmoodi; Hassan Heidari; Mansour Abdi (Iranian Journal of Educational Research)
Objective: The current investigation was carried out to explore the correlation between personality traits (specifically sensation seeking, assertiveness, psychological toughness), with the readiness for substance abuse in the male and female population of Arak city. Methods: Employing the correlation method, the study encompassed all married individuals in Arak city during 2023. The sample, comprising 400 participants (200 women and 200 men), was chosen through stratified random sampling. The research utilized four standardized questionnaires for data collection purposes. Results: Findings indicated a positive and significant association between sensation seeking and readiness for substance abuse among men, contrasting with the absence of such a link among women. While no connection was observed between psychological toughness and readiness for substance abuse in women, a reverse correlation was noted in men, where an escalation in toughness coincided with a reduction in readiness for substance abuse. Noteworthy was the significant relationship between assertiveness and readiness for substance abuse in women, which was not found in men. Conclusions: The results substantiate the notion that the mental well-being of parents may diminish their preparedness for engaging in substance abuse, consequently leading to positive impacts on the academic and emotional achievements of students.